THE REALIZATION OF THE CONCEPT OF "GREETING" IN ENGLISH, UZBEK, AND RUSSIAN INTERNET TEXTS - Khushmanova Shakhnoza Ibragimovna (Bright Mind Publishing, 2025)
The advent of the internet has transformed traditional forms of communication, including greetings, which are crucial for establishing social connection and politeness online. This study explores the realization of the concept of “greeting” in English, Uzbek, and Russian Internet texts, examining linguistic forms, cultural nuances, and pragmatic functions in digital communication. Using a corpus-based comparative approach, the research analyzes social media posts, online forums, chat messages, and comments to uncover how the conventions of greeting adapt to internet-mediated contexts. The findings reveal both universal online greeting strategies and language-specific, culturally embedded features that reflect broader sociocultural values. This study contributes to digital sociolinguistics, intercultural communication, and pragmatics by clarifying how “salom” functions linguistically and culturally across digital spaces in these three languages.
Keywords: Greeting, internet language, digital communication, sociolinguistics, English, Uzbek, Russian, intercultural pragmatics, language-specific, sociocultural values.